HPWS in the Public Sector: Are There Mutual Gains? - Michael White; Alex Bryson (Institute of Labor Economics (IZA), 2018)
Few studies investigate the links between high-performance work systems (HPWS) on public sector organizational performance and worker job attitudes. We fill this gap with analyses of these links using linked employer-employee surveys of workplaces in Britain in 2004 and 2011. We find robust evidence of positive associations between the use of HPWS and organizational performance in the public sector but no associations with worker attitudes. The implication is that, in contrast to similar work on the private sector in the United States (Appelbaum et al., 2000) HPWS is not delivering mutual gains for employers and employees in the British public sector.
Keywords: J28; L23; M50; M54; 330; public sector; HRM; HPWS; workplace performance; job satisfaction; organizational commitment; trust